The potential of facultative predatory Actinomycetota spp. and prospects in agricultural sustainability - Ibrahimi, Manar; Loqman, Souad; Jemo, Martin; Hafidi, Mohamed; Lemee, Laurent; Ouhdouch, Yedir (Frontiers in Microbiology, 2023)
Actinobacteria spp. in the phylum of bacteria have been explored extensively as sources of antibiotics and secondary metabolites. Besides acting as plant growth promoting agents, they also possess potential to control various plant pathogens however there are limited studies report the facultative predatory ability of Actinobacteria spp. Furthermore, the mechanisms that underline predation are poorly understood. We assessed the diversity of strategies activated by Actinobacteria species to attack and subsequently induce the cell lysing of their prey as a predatory organism. We revisited the diversity and abundance of secondary metabolites molecules linked to the different predation strategies by bacteria species. We analyzed the pros and cons of the distinctive predation mechanisms and explored the potential for development of diseases biocontrol for diseases suppression. The facultative predatory behaviors diverge from group attack “wolfpack”, cell-to-cell proximity “epibiotic’’ periplasmic penetration, and endobiotic invasion to degrade host-cellular content. The epibiotic represents the dominant facultative mode of predation, irrespective of the habitat origins. The wolfpack is the secondly used approach, the periplasmic and endobiotic invasion mechanisms are the lowest used strategy among the Actinobacteria harboring predatory traits. The secondary molecules as chemical weapons engaged in the respective attacks were reviewed. We finally explored the in the defining the sustainable biopesticides development to improve crop yield in the changing climate change.